Hepatic injury - Stracieri,Luis Donizeti da Silva (2006)
Hepatic trauma occurs in approximately 5% of all admissions in emergency rooms. The anatomic location and the size of the liver make the organ even more susceptible to trauma and frequently in penetrating injuries. The American Association for the Surgery of Trauma established a detailed classification system that provides for uniform comparisons of hepatic injury. Diagnosis of hepatic injury can be sometimes easy; however the use diagnostic modalities as diagnostic peritoneal lavage, ultrasound and computed tomography allow faster and more accurate diagnosis. Nonoperative management of the hemodynamically stable patient with blunt injury has become the standard of care in most trauma centers. Few penetrating abdominal lesions allow conservative management; exceptions can be some penetrating wounds to right upper abdominal quadrant. Operative treatment of minor liver injuries requires no fixation or can only be managed with eletrocautery or little sutures. Major liver injuries continue, despite technical advances, a challenge to surgeons. Many procedures can be done as direct repair, debridement associated to resections, or even in more severe lesions, packing. This constitutes a damage control which can allow time to recovery of patient and decreasing mortality shortly after trauma.